1997
DOI: 10.1038/bjc.1997.174
|View full text |Cite
|
Sign up to set email alerts
|

A polymer-based drug delivery system for the antineoplastic agent bis(maltolato)oxovanadium in mice

Abstract: Summary Using vanadyl sulphate, sodium orthovanadate or bis(maltolato)oxovanadium (BMOV), Cruz TF, Morgan A, Min W (1995, Mol Cell Biochem 153: 161-166) have recently demonstrated the antineoplastic effects of vanadium in mice. In this study, the antineoplastic effects of BMOV against human tumour cell lines was confirmed, and this effect was shown to depend on the prolonged exposure of the cells to the drug. We have investigated a polymeric drug delivery system for the sustained delivery of BMOV as an antin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…The inclusion of PEG in PCL beads has been shown to allow for concentration-dependent increases in the release rate of water-soluble drugs from such polymers [18]. In this study, drug-loaded bone cement films or beads that included PEG were observed to fragment easily under low manual pressure especially at concentrations of PEG greater than 10%.…”
Section: Resultsmentioning
confidence: 79%
“…The inclusion of PEG in PCL beads has been shown to allow for concentration-dependent increases in the release rate of water-soluble drugs from such polymers [18]. In this study, drug-loaded bone cement films or beads that included PEG were observed to fragment easily under low manual pressure especially at concentrations of PEG greater than 10%.…”
Section: Resultsmentioning
confidence: 79%
“…In addition, our pervious in vivo studies indicated that KynA is more potent than Kyn in suppressing the expression of fibronectin, which is essential for collagen deposition and assembly . Most importantly, the use of KynA would be safer even if it diffuses out into circulation because, (1) it is an end product in the Kyn pathway; therefore, there is no chance that it get metabolized to another product with unknown effect, and (2) its diffusibility through the blood brain barrier is very poor, which limits its accessibility to the central nervous system . Finally, KynA is far less water soluble than Kyn and easily dissolvable in organic solvents, such as DMF, which enable the use of organic‐based electrospinning process.…”
Section: Resultsmentioning
confidence: 99%
“…15,16 A polymer vanadium-based drug confirmed its potential as antineoplastic agent. 17 Liposoural surface-loading of water-soluble cationic iron(III) porphyrines allowed for a targeted necrosis of tumor cell. 18 Cobalt complexes exhibited selective effects on tumor tissue.…”
Section: Introductionmentioning
confidence: 99%